2012
DOI: 10.1016/j.eurpsy.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Costs in Patients With Generalised Anxiety Disorder: One-Year Retrospective Analysis of Data From National Registers in Sweden

Abstract: The high rate of polypharmacy, significant psychiatric comorbidity and widespread use of benzodiazepine-anxiolytics and medications not indicated for GAD suggest that the disease burden is high. Total direct costs associated with the disease were high but still likely to be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…32 A Swedish study of GAD patients in specialized outpatient care found that a high proportion were on hypnotic medications in addition to maintenance treatments on serotonin modulators, particularly so in the elderly. 33 The prognosis in anxiety disorders, particularly PTSD, is influenced by sleep problems. 34 Interestingly, one study noted that if poor sleep was addressed by hypnotic drug therapy in addition to anxiolytic therapy, the response of GAD patients improved.…”
Section: Insomnia In Gadmentioning
confidence: 99%
See 1 more Smart Citation
“…32 A Swedish study of GAD patients in specialized outpatient care found that a high proportion were on hypnotic medications in addition to maintenance treatments on serotonin modulators, particularly so in the elderly. 33 The prognosis in anxiety disorders, particularly PTSD, is influenced by sleep problems. 34 Interestingly, one study noted that if poor sleep was addressed by hypnotic drug therapy in addition to anxiolytic therapy, the response of GAD patients improved.…”
Section: Insomnia In Gadmentioning
confidence: 99%
“…37 A national health registry in Sweden was performed for all GAD patients treated in specialized psychiatric units during the calendar year 2006. 33 They incurred a cost per patient of SEK 5520 for medications, SEK 7698 for outpatient visits, and SEK 92,152 for those requiring inpatient treatment.…”
Section: Cost Of Illness Studiesmentioning
confidence: 99%
“…Generalised anxiety disorder (GAD) is a common and persistent mental disorder with a point or annual prevalence of 2.1 to 4.4% (Hunt et al, 2002;Grant et al, 2005;Remes et al, 2017;Ruscio et al, 2017). GAD is often present with other mental disorders such as depression, other anxiety disorders, insomnia and physical illness (Chapman et al 2010;Ruscio et al, 2017), all of which can lead to considerable health expenditure (Sandelin et al, 2013). According to the National Institute for Clinical Excellence (NICE) Guideline for Generalised Anxiety Disorder for England and Wales (NICE, 2011), the first step in the management of GAD is education about the condition and monitoring delivered in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…The third step NICE recommended intervention is either a high intensity psychological intervention such as individual cognitive behaviour therapy (iCBT), also delivered by IAPT services and relatively expensive, or drug treatment, initially with selective serotonin reuptake inhibitor antidepressants but if these are ineffective then more expensive drugs such as pregabalin are used. There can be a substantial delay before iCBT can be offered (Sandelin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For every patient seeking health care for anxiety symptoms, 22% are diagnosed with GAD, which utilizes large amounts of primary care resources (Wittchen, ). About 90% of patients with GAD have high degrees of comorbidity, with major depressive disorder (MDD) being the most common one at 60% (Sandelin, Kowalski, Ahnemark, & Allgulander, ). When patients with GAD additionally show symptoms of MDD, primary care rates often increase (Wittchen, ).…”
Section: Introductionmentioning
confidence: 99%